Correlation of Monoclonal Antibody Based Latex Agglutination Test with Haematological and Physiological Parameters for Diagnosis of Bubaline Trypanosomosis - Kumar, Pradeep; Vohra, Sukhdeep; Swain , Krutanjali; Sangwan, Arun K. (International Journal of Livestock Research, 2019)
Around 400 blood samples of buffaloes belonging to thirty villages in seven blocks of district Hisar, Haryana were screened for the presence of Trypanosoma evansi using Giemsa stained thin blood smears and monoclonal antibody based latex agglutination test (mAb-LAT). The haemoglobin (Hb; g/dL), packed cell volume (PCV; %) and the body temperature (oF) were also examined. Blood examination did not reveal any sample positive for T. evansi infection, however, mAb-LAT showed 95 (23.7%), 101 (25.2%), 84 (21.0%), 38 (9.5%) and 82 (20.5%) samples showing strong, moderate, weak positive, doubtful and negative reactivity, respectively. Significant differences were observed in Hb and PCV values between positive samples when compared to suspected and negative samples inmAb-LAT test, while for temperature significant difference was seen between positive and negative samples only. These results pointed towards lower sensitivity of blood smear examination over mAb-LAT test for diagnosis of bubaline trypanosomosis.